Regularity properties of viscosity solution of nonconvex Hamilton–Jacobi equations. Issue 6 (26th April 2019) - Hoang, Nguyen
ABSTRACT: Some properties of characteristic curves in connection with the viscosity solution of the Hamilton–Jacobi equation( H, σ ) defined by the Hopf formulau ( t, x ) = max q ∈ R n ⟨ x, q ⟩ - σ ∗ ( q ) - t H ( q ) are studied. We are concerned with the points at which the solution u ( t, x ) is differentiable, and the strip of the formR = ( 0, θ ) × R n in the domainΩ where u ( t, x ) is of classC 1 ( R ) .